1995
DOI: 10.1037/0022-006x.63.6.966
|View full text |Cite
|
Sign up to set email alerts
|

Researcher allegiance and meta-analysis: The case of cognitive therapy for depression.

Abstract: K. S. Dobson (1989) conducted a meta-analysis of 28 studies of cognitive-behavioral therapy for depression that used the Beck Depression Inventory as outcome measure. He concluded that the outcome of this type of therapy was superior to that of other forms of psychotherapy and to that of pharmacotherapy. The present study reanalyzed the same studies, and a further set of 37 similar ones published from 1987 to 1994, taking into account variations in sample size and researcher allegiance. This study confirmed Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
2
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 64 publications
2
131
2
6
Order By: Relevance
“…Dobson (1989) conducted the first meta-analysis on this topic and found CT to be superior to untreated controls, wait list, pharmacotherapy, behavior therapy, and a heterogeneous group other therapies. Gaffan, Tsaousis, and Kemp-Wheeler (1995) hypothesized that Dobson's findings were positively biased toward CBT by researcher allegiance; the tendency for authors to prefer one therapy to another. They reanalyzed the same set of studies reviewed by Dobson while controlling for researcher allegiance and found that researcher allegiance accounted for half the difference between CBT and other treatments.…”
Section: Depressionmentioning
confidence: 99%
“…Dobson (1989) conducted the first meta-analysis on this topic and found CT to be superior to untreated controls, wait list, pharmacotherapy, behavior therapy, and a heterogeneous group other therapies. Gaffan, Tsaousis, and Kemp-Wheeler (1995) hypothesized that Dobson's findings were positively biased toward CBT by researcher allegiance; the tendency for authors to prefer one therapy to another. They reanalyzed the same set of studies reviewed by Dobson while controlling for researcher allegiance and found that researcher allegiance accounted for half the difference between CBT and other treatments.…”
Section: Depressionmentioning
confidence: 99%
“…Early meta-analyses all showed CBT to be more effective than no treatment for people with depression, [4][5][6][7][8] although no firm evidence was found that CBT was any more or less efficacious than other psychotherapies or pharmacotherapy. No recent meta-analysis has specifically focused on effect studies of CBT, and examined potential effect moderators and other sources of heterogeneity.…”
Section: Limitationsmentioning
confidence: 99%
“…1,[3][4][5] If the intervention, especially if it corresponds to the diagnosis, would determine the outcome, this should not be so, and it also should not be that practically all therapeutic procedures, tested against each other in direct experimental comparisons, lead to very similar effects (the so-called Dodo bird effect). [5][6][7][8][9][10] This is particularly true when (i) only bona fide therapies were included, i.e. treatment procedures that are wellintentioned and realized by competent therapists as probably effective treatment methods (not only as half-hearted control conditions); and when (ii) the 'affiliation', i.e.…”
Section: Treatment Techniques and Technique-specific Factors Of Effecmentioning
confidence: 99%